“Blanche Isn’t Folklore”: Reflections on Ethnography as Relationship - Tye, Diane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
Searching to identify positive, constructive ways forward in the face of folkloristics’ colonialist past, here I return to fieldwork I completed on local characters in my home community of Amherst, Nova Scotia in 1986-87 near the beginning of my folklore career. In reflecting on the applicability of Indigenist research as outlined by Shawn Wilson (2008, 2019) to conventional folklore collecting practices, I consider ways the ethnography I conducted was embedded in relationships to place, people, and ideas. I question how my positioning as a folklorist both facilitated and hindered collaborative exchange and its implications for social change.